Branched-chain amino acids catabolism and cancer progression: focus on therapeutic interventions - Xu, Er; Ji, Bangju; Jin, Ketao; Chen, Yefeng (Frontiers in Oncology, 2023)
Branched-chain amino acids (BCAAs), including valine, leucine, and isoleucine, are crucial amino acids with significant implications in tumorigenesis across various human malignancies. Studies have demonstrated that altered BCAA metabolism can influence tumor growth and progression. Increased levels of BCAAs have been associated with tumor growth inhibition, indicating their potential as anticancer agents. Conversely, a deficiency in BCAAs can promote tumor metastasis to different organs due to the disruptive effects of high BCAA concentrations on tumor cell migration and invasion. This disruption is associated with tumor cell adhesion, angiogenesis, metastasis, and invasion. Furthermore, BCAAs serve as nitrogen donors, contributing to synthesizing macromolecules such as proteins and nucleotides crucial for cancer cell growth. Consequently, BCAAs exhibit a dual role in cancer, and their effects on tumor growth or inhibition are contingent upon various conditions and Formatted concentrations. This review discusses these contrasting findings, providing valuable insights into BCAA-related therapeutic interventions and ultimately contributing to a better understanding of their potential role in cancer treatment.Three essential amino acids, including valine, leucine, and isoleucine, are known as branched-chain amino acids (BCAAs). Evidence revealed that the metabolism of BCAAs could be associated with tumorigenesis in various human malignancies. Some studies reported that increasing BCAA levels inhibit tumor growth and progression. Furthermore, poor BCAA diets can be accompanied by tumor metastasis to other body organs because high concentrations of BCAAs affect tumor cell migration and invasion via downregulating N-cadherin, a promoter of tumor cell adhesion, angiogenesis, metastasis, and invasion. On the other hand, BCAAs, as nitrogen donors, generate macromolecules such as proteins and nucleotides essential for cancer cell growth. Therefore, it seems that BCAAs can have a dual role in cancer, and depending on the conditions and concentration, their effect on tumor growth or inhibition can be different. This review discussed these contradictions as well as summarized BCAA-related therapeutic interventions.